Natural history of nonalcoholic steatohepatitis/nonalcoholic fatty liver disease‐hepatocellular carcinoma: Magnitude of the problem from a hepatology clinic perspective. Issue 4 (October 2016) - D'Avola, Delia; Labgaa, Ismail; Villanueva, Augusto
Abstract : Watch a video presentation of this article